Hubungan Faktor Predispossing Enabling and Reinforcing dengan Praktik Safety Riding pada Kurir Ekspedisi Kota Semarang - Diana Yulianti; Bina Kurniawan; Ekawati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: Courier mailers and freight forwarding companies risk having a traffic accident while traveling to the customer's location. With the increasing demand for customers will be directly proportional to the increased risk of traffic accidents. Therefore couriers need to apply safety riding behavior. Based on Lawrence Green's theory, behavior is influenced by three factors, namely predispossing, enabling and reinforcing factors. Objectives: Analyzing the relationship between predisposing, reinforcing and enabling factors with the safety riding practice of the courier company in the city of Semarang Research Metodes: This research uses quantitative methods with cross sectional approach. The population in this study was 121 motorcycle couriers with a sample of 36 couriers using incidental sampling techniques. Statistical analysis using the chi square test. Results: The results showed that respondents with safe riding practices were 52.8%, respondents with long working periods were 83.3%, respondents with high school / vocational education levels were 72.2%, respondents with good knowledge were 55.6%, respondents with a positive attitude of 55.6%, respondents who have received safety riding training by 52.8%, respondents with vehicle conditions according to the standard of 50%, respondents who are influenced by superiors by 58.3% and who are influenced by colleagues employment by 61.1%. Conclusion: It can be concluded that 47.2% of respondents have not applied safety riding and 52.8% of respondents have applied safety riding. Based on the Chi Square test results, there are several variables related to safety riding practices, namely knowledge (p-value: 0.021), attitude (p-value: 0.003), training (p-value: 0.047), the role of superiors (p-value: 0.048), the role of co-workers (p-value: 0.020) and the condition of the vehicle (p-value: 0.019).